1989
DOI: 10.1007/bf01855036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclosporine on oxidative phosphorylation and adenylate energy charge of regenerating rat liver

Abstract: The effect of cyclosporin A (CyA) on regenerating liver was investigated in subtotal hepatectomized rats treated with CyA in terms of mitochondrial phosphorylative activity, hepatic energy charge, and serum bilirubin levels. In the CyA-treated hepatectomized group, the energy charge decreased from normal control value of 0.857 to 0.782 at 6 h after hepatectomy. The decreased energy charge, however, gradually increased and returned to 0.842 at 48 h after hepatectomy with no significant changes being observed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The involvement of ROS in cyclosporine toxicodynamics is well established ( Uemoto et al ., 1989 ; Wang & Salahudeen, 1994 ; Wolf et al ., 1997 ; Parra et al ., 1998 ; Cruz & Wolf, 2001 ). Our study added two important pieces of information: (A) compensatory mechanisms reducing the negative effects of cyclosporine on high‐energy phosphate metabolism is associated with a reduction in ROS concentrations and (B) the ROS scavenger tocopherol almost completely antagonizes the negative effects of cyclosporine on cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ROS in cyclosporine toxicodynamics is well established ( Uemoto et al ., 1989 ; Wang & Salahudeen, 1994 ; Wolf et al ., 1997 ; Parra et al ., 1998 ; Cruz & Wolf, 2001 ). Our study added two important pieces of information: (A) compensatory mechanisms reducing the negative effects of cyclosporine on high‐energy phosphate metabolism is associated with a reduction in ROS concentrations and (B) the ROS scavenger tocopherol almost completely antagonizes the negative effects of cyclosporine on cell metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our study gave additional insights into the mechanisms underlying the reduction of high‐energy phosphate concentrations by cyclosporine. Previously described mechanisms involved in the cyclosporine‐mediated reduction of cellular ATP concentrations include increased radical formation ( Uemoto et al ., 1989 ; Wang & Salahudeen, 1994 ; Wolf et al ., 1997 ) and mitochondrial Ca 2+ ‐overload ( Salducci et al ., 1996 ). The accumulation of oxaloacetate and lactate indicated that cyclosporine significantly inhibited the Krebs cycle at its entrance, possibly by inhibiting pyruvate dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine perfusate concentrations of 100 μg l −1 corresponded to the lower limit of the blood concentration range targeted in transplant patients (Oellerich et al ., 1995). Various previous studies (Gabe et al ., 1998; Henke et al ., 1992; Massicot et al ., 1997; Riuz‐Cabello et al ., 1994; Uemoto et al ., 1989) demonstrated that cyclosporine specifically inhibits mitochondrial energy production and decreases ATP level in target organs of its toxicity such as kidney, liver and intestine in vitro as well as in vivo . Impairment of energy metabolism in the brain results in excitotoxic neuronal death in various neurodegenerative illnesses (Beal, 1992).…”
Section: Discussionmentioning
confidence: 99%